Governance in the Italian Processed Tomato Value Chain: The Case for an Interbranch Organisation - Samoggia, Antonella; Monticone, Francesca; Esposito, Gianandrea (Sustainability, 2022)
Collective action among producers is a corrective measure for power imbalance, which affects primary producers in agro-food supply chains. As associations of producers and processors, Interbranch Organisations (IBOs) promote dialogue, best practice, and market transparency. However, interbranch cooperation is still a less explored subject in agro-food governance studies. Therefore, the present paper aims to analyse the role of IBO North Italy for Processing Tomato (IBO NIPT) in the governance of the processed tomato value chain. The IBO for Processing Tomatoes of Northern Italy was chosen as a case study as it is one of the eight recognized IBOs in the country and Italy is the third biggest producer of tomatoes for processing worldwide. Semi-structured interviews with stakeholders involved in the processed tomato value chain were carried out to reach this aim. Abridged transcripts were analysed through thematic analysis by two or three researchers. The present study has three research steps: first, to explore the history of the IBO NIPT; second, to explore its current role as collective institution acting towards power imbalances; third, the IBO’s role in reference price streamlining. A multi-theoretical approach based on the following three theoretical frameworks was used to analyse the interviews: New Institutional Economics (NIE); Devaux’s framework for collective action; and Transaction Cost Economics. The paper highlights the role of local institutions in bringing innovations in the food supply chain and suggests that the future of IBOs in Italy has to be expanded beyond reference price streamlining and could benefit from the cooperation of retailers.